QUALITY OF LIFE AND PHYSICAL ACTIVITY IN PATIENTS WITH CHRONIC HEART FAILURE. Issue 10 (10th June 2013) - Saavedra, Francisco; Alves, José; Oliveira, Liliana; Garrido, Nuno; Sousa, Nélson; Reis, Victor
Abstract : Background: Chronic heart failure is a complex syndrome manifested by hemodynamic disturbances, exercise intolerance, increased mortality and reduced quality of life (Heidenreich et al ., 2006). Besides impaired cardiac function, a variety of changes in peripheral skeletal muscles may contribute to the major and debilitating symptoms of chronic heart failure, dyspnea and fatigue (Coats et al ., 1994). The aim of this study was to evaluate the perception of quality of life and physical performance in patients with heart failure. Methods: A total of 47 patients, of both genders, with chronic heart failure, were recruited (55, 5±12, 3 years), and divided into two groups. One group (n=28) clinical and another group (n=19) surgical. Fifty five percent of the patients had NYHA class III and forty five percent NYHA class III. Quality of life was assessed, in both groups, with the Minnesota Living with Heart Failure Questionnaire (Rector et al; 1992). The physical activity level was measured by an accelerometer (number of steps) during seven consecutive days. Results: For the quality of life, were found significant differences (p ≤0.05), in the physical dimensions of chronic heart failure patients. The surgical group showed a better quality of life. Considering the physical activity, the clinical group appear with better performance (p≤0, 01). In the daily activities, there weren't observed vigorous or very vigorous intensity activities. Conclusions: These results indicate that chronic heart failure patients differ in their daily physical activity, especially in high-impact activities, due to age, gender, and disease progression (Rector, 2005). Further investigation should be directed towards the impact of the different components of the rehabilitation process upon quality of live improvement in patients with chronic heart failure.